Integrated weed management in soybean - Singh, R K (Indian Farming, 2018)
By adopting integrated weed management practices, farmers received higher yield (5 q/ha) that fetches higher income (Rupees 8,850/ha) due to reduction in weed density (7.66/m2) than farmers practices. Integrated Weed Management practices help in efficient utilization of available or given resources and improve the product by adopting integrated weed management practices. Farmers received higher yield (5 q/ha) that fatches higher income (Rupees 8,850/ha) due to reduction the weed density (7.66/m2) as compared to farmers practices. Integrated Weed Manage-ment practices help in efficient utilization of available or given resources and improve the product.